Rapid evolution of a bacterial parasite during outbreaks in two Daphnia populations. Issue 1 (16th January 2023) - Shaw, Clara L.; Duffy, Meghan A.
Abstract: Myriad ecological and evolutionary factors can influence whether a particular parasite successfully transmits to a new host during a disease outbreak, with consequences for the structure and diversity of parasite populations. However, even though the diversity and evolution of parasite populations are of clear fundamental and applied importance, we have surprisingly few studies that track how genetic structure of parasites changes during naturally occurring outbreaks in non‐human populations. Here, we used population genetic approaches to reveal how genotypes of a bacterial parasite, Pasteuria ramosa, change over time, focusing on how infecting P. ramosa genotypes change during the course of epidemics in Daphnia populations in two lakes. We found evidence for genetic change – and, therefore, evolution – of the parasite during outbreaks. In one lake, P. ramosa genotypes were structured by sampling date; in both lakes, genetic distance between groups of P. ramosa isolates increased with time between sampling. Diversity in parasite populations remained constant over epidemics, although one epidemic (which was large) had low genetic diversity while the other epidemic (which was small) had high genetic diversity. Our findings demonstrate that patterns of parasite evolution differ between outbreaks; future studies exploring the feedbacks among epidemic size, host diversity, and parasite genetic diversity would improve our understanding of parasite dynamics and evolution. Abstract : We examined the genetic structure and diversity of the parasite Pasteuria ramosa in two natural outbreaks using variable number tandem repeats to genotype the parasite in infected Daphnia dentifera hosts. We found evidence for parasite evolution within these outbreaks: the genetic distance between sampled parasite genotypes infecting hosts increased with time between sampling, but with notable differences between the two lakes. Although genotype diversity remained flat over time in both outbreaks, it was significantly higher in the lake with the smaller outbreak. This work is valuable for understanding evolution and patterns of parasite genetic diversity within outbreaks.